Posted by **tony** on Sunday, September 12, 2010 at 1:09pm.

We replace each occurrence of z with the number 4, and simplify

(1 + z) × 2 + 12 ÷ 3 - z

## Answer this Question

## Related Questions

- math - simplify square root of 116 rt(116) = rt(4*29) = 2rt(29) i need help with...
- math - Two events are _________ if the outcome or occurrence of the first ...
- math 116 - Simplify. -2[38-(-56-50)]=
- math 116 - I thought I knew this stuff but now I'm starting to wonder. I've ...
- Math 116 - simplify the expression -2(2z-7y)-z
- MATH 116 - Simplify ab2 for a=2 and b=3
- math 116 - 8x 4=4x 7 simplify this is what I come up with is this correct? x = 3...
- MATH 116 - Need the simplify or expression to this problem:.75 times 5 is 3.75.
- math - 1.Explain why there is no number that can replace N to make the equation...
- mat 116 - Simplify (2x)^3+2^3x

More Related Questions